Literasi Keuangan Syariah Pada Badan Usaha Milik Desa (BUMDes) Se-Kecamatan Tambang Kabupaten Kampar - Darnilawati Darnilawati; Nuryanti Nuryanti; Haniah Lubis (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
Village-Owned Enterprises or abbreviated BUMDes has a goal, one of which is to encourage rural economic activities. The management of BUMDes in the Tambang District still uses the conventional system. Therefore, it is necessary to provide an understanding of Islamic Finance. The purpose of this service is to increase the understanding of BUMDes managers regarding Syariah finance and motivate BUMDes managers to apply sharia principles, with the following materials: Sharia BUMDes finance, Islamic financial principles, Islamic financial products, sharia contracts. Also conducted pre-test and post-test. The results of community service activities, seen from the pre-test and post-test scores carried out, showed an increased understanding of Islamic finance among BUMDes managers in the Mining District, where the decrease in participants who scored below 50 and the increase in participants with a score of 71-100 showed that after the explanation from the dedicated team and the motivation provided showed an increase in understanding of Islamic finance and also showed the motivation of participants in understanding literacy, principles and, Islamic finance contracts.